Numerical Study Of Impact-Induced Elastic Wave Based Non-Destructive Test On Reinforced Concrete Structures Containing Delamination - Yong, Chee Lok (2021)
This study presents the development of a non-destructive test method for evaluating delamination defects in reinforced concrete by the impact-induced elastic wave using four sensor accelerators and a signal acquisition unit (USB3100 Series). A laboratory experiment was conducted to obtain the waveform result of different sizes and depths of delamination defects from different steel ball diameters. The propagated wave was interpreted numerically to determine the behaviour and characteristic of the Rayleigh wave (R-wave) by using Matrix Laboratory (MATLAB). Through the simulation of data, time-domain and frequency-domain graphs were obtained by using the highest magnitude of amplitude of the R-wave and Fast Fourier Transform, which were then used to determine the experimental measurement of concrete specimens. The correlations of velocity, amplitude attenuation and peak frequency were calculated to estimate the location, size and depth of the delamination defects with acceptable discrepancies due to the nature of reinforced concrete. Through the analysis of the result, the velocity of the R-wave has reduced from sensor 2 to sensor 3 in the sound concrete, whereas the velocity of the R-wave remains unchanged or increased along with the sensors. This phenomenon justifies the location of delamination defects. The attenuation rate of the R-wave is said to increase as the wave’s frequency increases but decreases as the diameter of the steel ball increases. Furthermore, the peak frequency of R-wave is used to evaluate the depth of delamination where a greater value of peak frequency shows deeper delamination or vice versa. However, some of the results obtained are insensitive to evaluate the parameter of delamination defects. Despite the insensitive results, the study still provided a trends to evaluate R-wave behaviour in the concrete structure.